Environmental & architectural phenomenology. Vol. 23, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2012)
Vol. 23, No. 3, Fall 2012 (includes “items of interest,” “citations received,” book reviews by David Seamon & Benoît Jacquet, and essays by Reza Shirazi & John Cameron).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals